A nossa luta é essa: uma etnografia com as lutas de moradores(as) removidos(as) pelo Programa de Urbanização de Favelas numa área entre a favela de Heliópolis e São João Clímaco - Guidotti, Marcos Vinícius Silva (Universidade Federal de São Carlos, 2026)
In this research, conducted in the area of the Heliópolis favela and the São João Clímaco neighborhood (southern zone of São Paulo), an ethnographic study was carried out on the effects of the national policy of recent decades aimed at combating precarious settlements – understood from the development of the Favela Urbanization Program – specifically its housing and social interventions. To achieve this objective, the thesis is structured into five chapters that articulate theoretical, documentary, and ethnographic analysis. The first chapter ethnographically reconstructs the formation of the field of urban studies, demonstrating how the central lens defining favelas as spaces of precarious housing was consolidated, focusing on the theoretical/discursive bases that would later be assimilated by the national public housing policy studied. The second chapter specifically examines the transition of this alignment between the theory of urbanization (of large cities) and housing policies, analyzing the theoretical-political fold through which the critical diagnosis of the unequal city – forged in the struggles against the military dictatorship – was converted into housing management technology, focusing on the description of how this academic knowledge underpinned the national policy to combat precarious settlements in urban Brazil (materialized in the Favela Urbanization Program). The third chapter introduces the ethnographic perspective of the research field, describing the historical action of residents who formed the local social movement in the Heliópolis region and their influence on the territorialization of the Favela Urbanization Program's intervention, explaining how local housing struggles were both recognized and resignified by the Program. The fourth chapter complicates this understanding by presenting other voices, knowledges, and housing arrangements that escaped the standardizing planning of the Favela Urbanization Program, pointing to the diversity and complexity of the ways of living in the favela that were obscured by the housing intervention studied. Finally, the fifth chapter focuses on the concrete experience of removal and waiting resulting from the intervention, detailing ethnographically how the lives of residents of the studied area were transformed by forced displacement, dependence on housing assistance programs, and prolonged uncertainty regarding the housing promised with the development of the Favela Urbanization Program; which, according to statements gathered in the research, produced a new form of vulnerability. The research, based on intensive fieldwork and bibliographic and documentary research, made it possible to confront the official project of the city with the understandings of struggle held by the population objectified by that project. The thesis concludes that urban interventions such as the Favela Urbanization Program, by ignoring the complexity, history, and disputes inherent in the ways of living in favelas, not only fail to solve housing problems but often intensify them, demanding from favela residents constant reinventions of their struggles for the right to housing and to live in the city.
This is our struggle: an ethnography centering on the struggles of residents displaced by the Favela Urbanization Program in an area between the Heliópolis favela and São João Clímaco
Nuetra lucha és esta: una etnografía de las luchas de los residentes desplazados por el Programa de Urbanização de Favelas en una área entre la favela de Heliópolis y São João Clímaco.
Keywords: Remoção Habitacional; Favela; Urbanização de Favelas; Luta Habitacional; São Paulo; Housing Displacement; Slum; Slum Upgrading; Housing Struggle; Desplazamiento Habitacional; Favela; Urbanización de Favelas; Luchas por la Vivienda; São Paulo; CIENCIAS HUMANAS::ANTROPOLOGIA::ANTROPOLOGIA URBANA; 10. Redução das Desigualdades